Folie a deux - Pratikshya Chalise; Sandip Subedi; Pawan Sharma (Journal of Nepal Medical Association, 2015)
Shared psychotic disorderis a rare psychiatric disorder. It is defined when a primary psychotic person imposes his/her delusional beliefs to the other person usually in a close relationship. Occurrence of this disorder among family members and close friends has been described. However, its exact incidence and prevalence is not known. Since such case has not been reported in Nepal to best of our knowledge, we present a case of shared delusional disorder along with brief review of literature. This case report describes a case of common shared persecutory delusion in husband and wife.